Preparation of tetra-substituted In(III)Cl and metal-free phthalocyanines containing benzotriazole groups and investigation photophysicochemical properties - Penlik, Yunus; Avciata, Oguzhan; Gorduk, Semih (ELSEVIER SCIENCE SA, 2025)
In this study, tetra-substituted metal-free and In(III)Cl phthalocyanine compounds containing 2-(5-chloro-2benzotriazolyl)-6-tertbutyl-p-cresol (Tinuvin-326) group were synthesized and their photophysicochemical properties were investigated for the first time. This study was performed in three steps. In the first step, a new 2(5-chloro-2-benzotriazolyl)-6-tertbutyl-p-cresoldicyanobenzene (4TpC) structure was synthesized and this compound was characterized by various methods. In the second step, peripherally tetra-substituted metal-free (4TpC-H2Pc) and In(III) (4TpC-InPc) phthalocyanine compounds were synthesized using 4TpC compound and these compounds were characterized using different instrumental methods. In the last step, the aggregation, photophysical and photochemical properties of 4TpC-H2Pc and 4TpC-InPc compounds were investigated and their suitability as photosensitizers for PDT studies was determined. After photochemical studies, singlet oxygen quantum yields were calculated in DMF (0.18 for 4TpC-H2Pc and 0.68 for 4TpC-InPc) and DMSO (0.21 for 4TpC-H2Pc and 0.72 for 4TpC-InPc) solvents. From these results, it is concluded that the synthesized phthalocyanine compounds are suitable compounds as photosensitizers in PDT studies.
Keywords: Phthalocyanine; Photophysicochemical; Tinuvin-326; In(III)Cl; Metal-free; PHOTOCHEMICAL PROPERTIES; ZINC(II); DERIVATIVES; PARAMETERS; POSITIONS; Chemistry